Survey on outcomes of emergency standing caesarean section in equids - de la Rebière de Pouyade, Geoffroy; Binard, Maureen; Deleuze, Stéfan; Ponthier, Jérôme (Frontiers in Veterinary Science, 2025)
IntroductionStanding caesarian section (C-section) in mares is poorly documented in the literature. It is reportedly straightforward to perform for veterinarians experienced in bovine practice and is more accessible and less expensive than recumbent techniques. The study aimed to create a survey to report the outcomes of in field C-section through a flank laparotomy with the mare standing under sedation.MethodsA survey was developed for field veterinarians practicing standing C-sections. Data were collected regarding the veterinarian’s experience and practice type, details about the mare and the reasons for performing the standing C-section in the field, the mare’s condition during the procedure, as well as information on asepsis protocols, anesthesia, surgical techniques, medications used, and the follow-up of complications, including the survival outcomes of both the mare and the foal. Complication and survival rates were then used to determine potential risk factors. Fisher’s exact tests were used, and significance was set at p < 0.05.Results35 questionnaires, each addressing one C-section case, completed by a total of 19 veterinarians were considered. The most important factor for performing the surgery was the economic concern. The main postoperative complication of the surgery was infection/dehiscence of the wound (12/34). The mare survival rate at 1 year was 74% (25/34). The foal survival rate at 6 months was 20% (7/35). More live foals were delivered when dystocia lasted less than 2 h.ConclusionThis survey shows that performing a standing C-section in the field might be a viable technique, both economically and in terms of mare’s and foal’s survival.